The correlation between prenatal maternal active smoking and neurodevelopmental disorders in children: a systematic review and meta-analysis - Danrong Chen; Qing Niu; Shiping Liu; Wenchuan Shao; Yi Huang; Yifan Xu; Yihan Li; Jiani Liu; Xu Wang; Haibo Yang (BMC Public Health, 2023)
Abstract Objective To systematically evaluate the association between maternal active smoking during pregnancy and Tourette syndrome (TS), chronic tic disorder (CTD), and developmental coordination disorder (DCD) in children, and to provide evidence-based medical references to reduce the incidence of neurodevelopmental disorders in children. Method We searched PubMed, Web of Science, Embase, and Cochrane Library to obtain relevant articles published before 4 August 2021. Two reviewers independently assessed the articles for eligibility and extracted data. Results We included eight studies involving a total of 50,317 participants (3 cohort, 3 case–control, and 2 cross-sectional studies). The pooled effect estimates suggested that prenatal maternal active smoking is related to an increased risk of neurodevelopmental disorders (OR = 1.91, 95% CI: 1.30–2.80), especially DCD (OR = 2.25, 95% CI: 1.35–3.75). Maternal active smoking during pregnancy is not associated with TS (OR = 1.07, 95% CI: 0.66–1.73) in children. Conclusion In this meta-analysis, we found evidence for a correlation between active smoking exposure in pregnant women and neurodevelopmental disorders in children. Owing to the differences in sample size, smoking categories and diagnostic methods, further research is needed to validate our results.